إسهامات حوكمة الشركات في تطوير وظيفة المراجعة الداخلية - تجانية, حمزة; لبزة, هشام; ضيف الله, محمد الهادي (جامعة الوادي - University of Eloued, 2020)
هدف هذه الورقة البحثية لدراسة إسهامات وانعكاسات مفهوم حوكمة الشركات على تطوير وظيفة المراجعة الداخلية، وذلك من خلال أن المراجعة الداخلية تعتبر صمام الأمان للشركات، للحد من أسباب الانهيار وأزمة الثقة التي أثرت على أغلب التعاملات في الأسواق العالمية والتي كان من أهم مسبباتها الرئيسية هو التضليل وضعف مستوى المراجعة الداخلية، مما أدى إلى فقدان الثقة في إدارات ومجالس إدارات الشركات والأنظمة الرقابية والمحاسبية المتبعة في تلك الشركات. وكان أهم أثر لانعكاسات حوكمة الشركات على وظيفة المراجعة الداخلية أنها أصبحت تعمل على زيادة قيمة الشركة والعمل على تحقيق أهدافها، وتقييم فاعلية إدارة المخاطر، والرقابة والمحافظة على أموال المالكين. This paper aims to study the contributions and implications of the concept of corporate governance to the development of the internal audit function. Internal auditing is considered the safety valve for companies to reduce the causes of collapse and the crisis of confidence that affected most transactions in international markets. The level of internal audit, which led to the loss of confidence in the departments and boards of companies and the regulatory and accounting systems used in those companies. The most important impact of corporate governance on the internal audit function has been to increase the value of the company and work towards achieving its objectives, assessing the effectiveness of risk management, and controlling and maintaining the owners' money.
Corporate governance contributions in the development of the internal audit function
مقال
Keywords: حوكمة الشركات، المراجعة الداخلية، لجنة المراجعة